Time Impact Analysis for Change Orders: Methodologies for Efficient Dispute Resolution - Rohit Shinde (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Time Impact Analysis (TIA) is a widely used methodology for assessing the effects of change orders on project schedules in construction projects. This paper explores various TIA methodologies, including retrospective, prospective, and hybrid approaches, and evaluates their effectiveness in providing accurate and efficient dispute resolution. By examining real-world case studies and legal frameworks, the paper identifies best practices in implementing TIA for mitigating disputes related to schedule delays. The study highlights the importance of detailed documentation, clear communication, and robust analysis techniques in ensuring that change orders do not adversely impact project timelines. The findings emphasize that adopting the appropriate TIA methodology can significantly reduce the risk of conflicts and support fair resolution processes in construction disputes.